Penilaian Kerentanan Air Tanah terhadap Pencemaran dengan Menggunakan Metode DRASTIC di Daerah Imbuhan Cekungan Air Tanah Jakarta - Dyah Laksmi Wahyusetyaningtyas; Hari Siswoyo; Taat Setiawan; Faizal Abdillah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The CAT Jakarta is a critical water resource that extends across several provinces in Indonesia, covering DKI Jakarta, Banten, and West Java. This basin comprises both recharge and discharge areas that support human settlements and various economic activities. The recharge area in CAT Jakarta covers 321.4 km2 and is densely populated, raising concerns about groundwater contamination. The study used the DRASTIC method to assess groundwater vulnerability, with seven parameters: Depth to Water Table (D), Net Recharge (R), Aquifer Media (A), Soil Media (S), Topography (T), Impact of the Vadose Zone (I), and Hydraulic Conductivity of the Aquifer (C). The vulnerability index obtained that 36.51% of the research area has a low vulnerability level, with values ranging from 101 to 119. The remaining 63.49% has a medium level of vulnerability, with values ranging from 120 to 157. These results suggest that the CAT Jakarta recharge area is at risk of contamination from pollutants with low to moderate intensity. Therefore, it is crucial to monitor and regulate activities that involve the use of groundwater in the area to prevent contamination. This study can guide policymakers and stakeholders in implementing effective management strategies for sustainable groundwater utilization in the CAT Jakarta basin.